2015
DOI: 10.4236/ojtr.2015.32005
|View full text |Cite
|
Sign up to set email alerts
|

Does Topical Agent Help Fracture Healing? A Pilot Study Using a Herbal Patch

Abstract: To observe the safety and effectiveness of a topical herbal agent used to promote fracture healing, a herbal patch containing extracts of three herbs, viz., Flos Carthami, Radix Dipsaci, Rhizoma Rhei and Borneolum Syntheticum (an enhancer) was applied on ten subjects with un-displaced fifth metatarsal fractures. Pain scores, foot and ankle function questionnaires and regional swelling were carefully assessed and recorded. Peripheral blood was taken to measure the inflammation cytokines. Assessment checks were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The topical treatment for all three sites had been very well accepted by patients. Recurrences after cessation of local treatment were observed in some cases, but the intensities were apparently much less than before treatment ( Tse et al, 2015a , b ).…”
Section: Research On Topical Agentsmentioning
confidence: 99%
“…The topical treatment for all three sites had been very well accepted by patients. Recurrences after cessation of local treatment were observed in some cases, but the intensities were apparently much less than before treatment ( Tse et al, 2015a , b ).…”
Section: Research On Topical Agentsmentioning
confidence: 99%
“…The amalgamation of the three carefully selected herbs resulted in an herbal paste aptly named CDR, derived from the abbreviation of their respective names. Clinical trials have demonstrated the efficacy of topically applying CDR for the treatment of conditions such as fifth metatarsal fractures and plantar fasciitis [ 23 , 24 ]. Furthermore, our research group has shown that when used in conjunction with oral pharmaceutical agents, CDR exhibits an additive effect, facilitating the healing process of fractures [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CDNR was then further optimized to a 3-herb formula: CDR (Notoginseng Rhizoma was excluded). A clinical trial on the efficacy of the CDR herbal paste in the treatment of the fifth metatarsal fracture has been conducted recently [ 28 ]. The results showed that the pain was soothed after two weeks of treatment.…”
Section: Introductionmentioning
confidence: 99%